Pengaruh Profitabilitas, Growth Opportunity, Struktur Modal Terhadap Nilai Perusahaan Subsektor Pertanian yang Terdaftar di Bursa Efek Indonesia Tahun2015-2019 - Mayang Deka Sentari (JURNAL ILMIAH EDUNOMIKA, 2021)
This study uses the variables of profitability, growth opportunities, and capital structure on firm value. The choice of these four variables is due to differences in previous research or what is commonly referred to as the research gap. The research objective was to determine the effect of profitability, growth opportunities, and capital structure on firm value in the agricultural sub-sector listed on the Indonesia Stock Exchange for the 2015-2019 period. The population in this study in the agricultural sub-sector listed on the Indonesia Stock Exchange for the 2015-2019 period was 7 companies, with a sample size of 35 companies. This study uses multiple linear regression analysis techniques in data processing where this technique is used to estimate the value of the dependent variable by using more than one independent variable. The analysis found that profitability had a negative and significant effect on firm value. There is a negative and significant effect on growth opportunity on firm value. Capital structure has a positive and significant effect on firm value. Keywords : Profitabilitas; growth opportunity; Capital structure; firm value